Pertumbuhan Ikan Patin Siam (Pangasius hypophthalmus) Dipelihara dalam Sistem Bioflok dengan Frekuensi Pemberian Molase yang Berbeda - Safir, Muhammad; Widyawati, Ni Made; Rizal, Achmad; Serdiati, Novalina (Journal Galung Tropika, 2023)
Biofloc technology requires an additional carbon source (molasses) to balance the C/N ratio to support the bacteria's performance. The application of molasses should be done with sufficient time and concentration to guarantee the excellent condition of the floc. This study aims to determine the appropriate frequency of molasses application for the growth of siamese catfish (P. hypophthalmus) using Biofloc System Technology. The study used a completely randomized design of flour treatments and five replications. The frequency of molasses application was aimed to find the optimum results of applying it once a day (A), every two days (B), every three days (C), and every four days (D), each in the corresponding experimental units. The experiment was carried out in 35 days. The feed given was 5% of body weight, with a feeding frequency of twice daily. The results showed no difference in growth (weight) and feed efficiency for all treatments. However, it was found that the amount and nutrient content of the formed floc were more stable when molasses was given at a frequency every two days (treatment B) until the sixth week compared to other treatments. In conclusion, the frequency of giving molasses for flock growth twice a day can be applied for siamese catfish using the Biofloc system.